HEART RATE VARIABILITY IN ATHLETES - Mytskan, B. M; Ostapiak, Z. M.; Mytskan, T. S.; Korobeinikov, H. V.; Drozd, S.; Tsynarskyi, V. Ya. (Rehabilitation and Recreation, 2022)
Purpose – analysis of physiological bases and evaluation of the effectiveness of the application of heart rate variability indicators in athletes. Methods. System-functional analysis of special literature and materials of the Internet (PubMed, Google Scholar) for the last ten years. Results. The scientific achievements in the study of heart rate variability in athletes are quite significant. Regular exercise and sports contribute to functional and structural changes in the central and peripheral mechanisms of the cardiovascular system. Studies comparing heart rate variability between sedentary and active subjects or athletes in different sports have shown different heart rate variability profiles, suggesting the possibility of monitoring heart rate variability performance to improve physical and physiological conditions.Heart rate variability performed immediately after exercise reflects the characteristic reactions that indicate whether the load corresponds to the athletic training of the athlete, but in athletes with high endurance skills and / or athletes with a long history of training, the algorithm of changes in heart rate variability does not always correspond. Exercise intensity is a major factor influencing HRV, with greater intensity causing lower heart rate variability during exercise, and the volume of muscles involved in training and / or energy expenditure being determinants of parasympathetic reactivation after exercise. "Complete autonomic dystonia" in most athletes with overtraining reflects a more advanced stage of maladaptation associated with suppressed regulatory function of the autonomic nervous system, both sympathetic and vagal effects. Conclusion. Thus, today there are not enough experimental works that could explain the mechanisms of changes in heart rate variability during intense and prolonged training in highly qualified athletes. However, this would make it possible to expand the application of the results of the diagnosis of heart rate variability in athletes to plan the duration, frequency and intensity of physical activity.